1994
DOI: 10.1111/j.1945-5100.1994.tb00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Acfer 217‐A new member of the Rumuruti chondrite group (R)

Abstract: Abatract-F'reviously, three meteorites from Australia and Antarctica were described as a new chondritic "grouplet" ( Acfer 217 is a regolith breccia consistimg of up to cm-sized clasts (=33 ~01%) embedded in a fme-grained, well-limed clastic matrix. The most abundant mineral is olivine (a72 vol%), which has a high Facontent of 37-39 mol%. The major minerals (olivine, Iow-Ca pyroxene, Ca-pyroxene, and plagioclase) show some compositional variability indicating a slightly unequilibrated nature of the meteorite.C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 31 publications
2
70
0
Order By: Relevance
“…Cosmic rays penetrate to depths equivalent to 40 g/cm 2 (Eugster 1988). Bischoff et al (1994) suggested that the cosmogenic nuclide ratios for Acfer 217 and Carlisle Lakes are consistent with exposure in relatively small (15-65 cm or 25 cm, respectively) radius bodies that experienced only a single-stage exposure history. These rocks were apparently well shielded from cosmic rays until they were ejected from the R chondrite parent body.…”
Section: Solar Cosmogenic and Radiogenic Gasesmentioning
confidence: 92%
See 1 more Smart Citation
“…Cosmic rays penetrate to depths equivalent to 40 g/cm 2 (Eugster 1988). Bischoff et al (1994) suggested that the cosmogenic nuclide ratios for Acfer 217 and Carlisle Lakes are consistent with exposure in relatively small (15-65 cm or 25 cm, respectively) radius bodies that experienced only a single-stage exposure history. These rocks were apparently well shielded from cosmic rays until they were ejected from the R chondrite parent body.…”
Section: Solar Cosmogenic and Radiogenic Gasesmentioning
confidence: 92%
“…However, individual clasts within the meteorites preserve higher shock grades. For example, the matrix and bulk of Rumuruti and Acfer 217 have shock grades of S2, but some fragments have olivine with planar fractures typical of shock stage S3 (Schulze et al 1994;Bischoff et al 1994). The majority of PCA 91002 is of shock stages S3-S4, but a range of shock grades, from S2-S5 (S5 = maskelynite), is preserved in its coarse-grained olivine grains (Rubin and Kallemeyn 1994).…”
Section: Shockmentioning
confidence: 99%
“…The fO 2 of lunar magmas is low and relatively constant at iron-wüstite (IW−0.5 ± 1.0) as indicated by the fairly ubiquitous presence of Fe-rich metal (Sato et al 1973;Usselman and Lofgren 1976;Haggerty 1978;Sato 1978;Nicholis and Rutherford 2005). With the notable exception of the Martian meteorites, the R chondrites (Nakamura et al 1993;Bischoff et al 1994;Rubin and Kallemeyn 1994;Schulze et al 1994;Kallemeyn et al 1996), and some carbonaceous chondrite groups (e.g., Larimer and Wasson 1988;Brearley and Jones 1998), most meteorite parent bodies also have compositional characteristics (Femetal phases) requiring they crystallized at fO 2 values of IW or below (e.g., eucrites : Stolper 1977, acapulcoites and lodranites: Benedix andLauretta 2006, ureilites: Walker andGrove 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Acfer 217 classified as a member of the Rumurutitype chondrite group (R) is another interesting sample that has been discussed in more detail previously [19]. Therefore here we present only the conclusions which can be made on the basis of model calculations for Acfer 217: The concentrations of all cosmogenic nuclides can be consistently interpreted only if a preatmospheric radius between 15 and 65 cm, a Single stage exposure history and a terrestrial age low compared to the half-life of are assumed.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 contains the results of determinations via y-y-coincidence spectrometry of some ordinary chondrites from the Acfer region, which predominantly were performed for a comparison with results of AMS measurements. The Classification of the meteorites indicated in the tables was done by Bischoff et al [17], For some of the meteorites, exposure ages based on ^'Ne determinations [10,18,19] are available. These ages are included in the last column of Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%